Organizational Citizenship Behaviors (OCB) in the Context of Big Five Employee Personality Traits - Marta MLOKOSIEWICZ (Communications of International Proceedings, 2021)
The article presents a review of the research results available in literature on the subject regarding relations between the personal traits of employees and their OCBs, taking into account three dimensions of such behaviors: OCB-I (individual-oriented), OCB-O (organization-oriented) and OCB-CH (change-oriented). The analysis covers the so-called Big Five personality traits: conscientiousness, agreeableness, openness to experience, extroversion / introversion, and emotional stability / emotional instability or neuroticism. The research material are five meta-analyses and three studies based on smaller samples. A major positive relation of these personality features with OCB has been confirm, except for negative affectivity / neuroticism which have a negative relation with OCB. Furthermore, the analyzed personality traits had a diversified effect on the identified OCB dimensions. The summary presents the possible further directions of research related to OCB and personality traits.
Keywords: Organizational Citizenship Behaviors; Intra-Organizational Relations; Employee; Management